(Electro)Chemical Processes of Poly(Ethylene Oxide)‐Based Electrolyte on Cu Surface during Lithium Secondary Battery Operation. Issue 3 (11th January 2023) - Yamada, Koki; Tsutsumi, Hiromori; Katayama, Yu
Abstract : Understanding the surface electrochemistry of polymer electrolytes under battery operating conditions is of great importance for tuning the solid electrolyte interphase (SEI) in lithium batteries with polymer electrolytes. Herein, the surface (electro)chemical process of poly(ethylene oxide) (PEO) lithium bis(trifluoromethanesulfonyl)amide (LiTFSA) (PEO10 LiTFSA) electrolyte on the Cu electrode is studied by operando attenuated total reflection infrared (ATR‐IR) and ex situ X‐ray photoelectron spectroscopy (XPS) techniques coupled with the interfacial resistance obtained from electrochemical impedance spectroscopy (EIS). Linear sweep voltammogram of the Cu electrode in PEO10 LiTFSA electrolyte suggests the SEI‐like layer formation involves three reduction steps. Operando ATR‐IR, ex situ XPS, and EIS reveal the corresponding (electro)chemical processes and their effect on the interfacial resistance; LiTFSA and residual H2 O and CO2 are first reduced, forming an inorganic SEI‐like layer without affecting the interfacial resistance. Subsequently, the PEO matrix reduces into several decomposed products, including CC components, responsible for the most resistive SEI‐like layer. Finally, PEO‐decomposed species with CC components further reduce into alkyl‐related species, leading significant reduction of the resistance of the SEI‐like layer. The study successfully reveals the complex surface (electro)chemical process at the PEO electrolyte–Cu electrode interface, and may serve as a model system for understanding SEI component and interfacial resistance relationship in the polymer electrolyte system. Abstract : The surface (electro)chemical process of poly(ethylene oxide) (PEO) lithium bis(trifluoromethanesulfonyl)amide (LiTFSA) (PEO10 LiTFSA) electrolyte on the Cu electrode is studied by operando attenuated total reflection infrared and ex situ X‐ray photoelectron spectroscopy techniques coupled with the electrochemical impedance spectroscopy. Herein, the interfacial resistance is successfully connected with the complex surface (electro)chemical process at the PEO electrolyte–Cu electrode interface.